1987
DOI: 10.3109/10641968709160027
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Autonomic Neuropathy in the Elevation of Inactive Renin in Diabetes Mellitus

Abstract: Plasma renin activity (PRA) and inactive renin(IR, activated by trypsin) were measured in the plasma of 15 type II diabetics with autonomic neuropathy (group 3), 15 type II diabetics without (group 2), and 14 nondiabetic control subjects (group 1) in the recumbent position. There were no significant differences between the 3 groups with respect to age, ideal body weight, supine resting mean blood pressure, serum creatinine, daily urinary excretion of sodium, or renin substrate at the time of study. Autonomic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…This is in agreement with previous findings in which renin activity assay was utilized [16,17]. Misbin et al [16] demonstrated that plasma prorenin is also significantly increased in patients with autonomic dysfunction, while Danser et al [14] did not find any significant changes in nondiabetic patients with chronic autonomic neuropathy.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This is in agreement with previous findings in which renin activity assay was utilized [16,17]. Misbin et al [16] demonstrated that plasma prorenin is also significantly increased in patients with autonomic dysfunction, while Danser et al [14] did not find any significant changes in nondiabetic patients with chronic autonomic neuropathy.…”
Section: Resultssupporting
confidence: 81%
“…Plasma inactive renin, viz. prorenin, has been of interest because of its significant increase in certain pathological states including renin secreting tumors [9,10] and diabetes mellitus [11,12] has been reported to be significantly increased [11,12] and to correlate with diabetic complications [12][13][14][15][16][17] Plasma prorenin has been determined by enzyme kinetic assay after activation by various pretreatments [1][2][3][4] in which the angiotensin I generated by plasma in vitro is measured by radioimmunoassay. The plasma renin activity, however, can be affected by the amount of plasma angiotensinogen.…”
mentioning
confidence: 99%
“…In the diet group, two patients had been diagnosed with diabetic retinopathy (one with background retinopathy and the other proliferative retinopathy), two had been diagnosed with overt nephropathy (microalbuminuria more than 200 btg/min), and, two with macroangiopathy (angina pectoris and aortic calcification, respectively). In the sulphonylurea group, seven patients had been diagnosed with diabetic retinopathy (two with background, one with preproliferative, and four with proliferative retinopathy, respectively), three had been diagnosed with neuropathy with weak patellar and Achilles tendon reflexes, decreased motor nerve conduction velocity, and abnormal expiration/inspiration ratio [16] which was assessed by measuring the ratio of the longest to the shortest R-R interval during deep breathing. Three patients had been diagnosed with nephropathy (proteinuria), and three with macroangiopathy (one with angina pectoris, and two with aortic calcification, respectively).…”
Section: Subjectsmentioning
confidence: 99%
“…Both Type 1 and Type 2 diabetes have been associated with high plasma levels of prorenin, either because of abnormal processing or secretion in the juxtaglomerular cells [6], or due to production of prorenin by other organs [7]. In diabetes, high prorenin concentrations have been associated with the microvascular complications of retinopathy [8], nephropathy [9] and neuropathy [10]. However, whether prorenin has any influence on activity of the renin angiotensin system once it has appeared in the circulation is not established.…”
Section: Introductionmentioning
confidence: 99%